`Setting the Benchmark` Part 3: Contextualizing the Match Demands of Specialized Positions at the FIFA Women`s World Cup Australia and New Zealand 2023 - Bradley, P. S. (Biology of Sport, 2025)
This study aimed to benchmark the match demands of specialised positions at the FIFA Women`s World Cup Australia and New Zealand 2023. With FIFA`s official approval, all sixty four games at the tournament were analysed using an optical tracking system alongside FIFA`s Enhanced Football Intelligence metrics. During a typical match, defensive and central midfielders covered 5-15% more total distance than centre backs, wide defenders and centre forwards (P < 0.01; Effect Size [ES]: 0.6-1.8). The distances covered at higher intensities (=19.0 and =23.0 km · h-1) were 18-89% and 88-163% greater in attacking midfielders, wide midfielders, wide forwards and centre forwards than other positions (P < 0.01; ES: 0.5-2.0 and ES: 1.0-1.3, respectively). Regarding offers made to receive the ball, defensive and central midfielders, attacking midfielders and centre forwards moved more between the lines than centre backs, wide defenders and wide midfielders (P < 0.01; ES: 1.0-1.9). Movements in behind lines were more common for offensive roles such as attacking midfielders, wide midfielders, wide forwards and centre forwards than other positions (P < 0.01; ES: 0.9-2.3). Regarding pressing events, direct pressure was highest for defensive and central midfielders compared to other positions (P < 0.05; ES: 0.5-1.3) and indirect pressure was greater for central midfielders, attacking midfielders, wide midfielders and centre forwards compared to centre backs and wide defenders (P < 0.01; ES: 0.9-2.3). A basic within tournament positional comparison revealed that centre backs and centre forwards demonstrated pronounced changes in their relative sprint distances from Canada 2015, France 2019 through to Australia and New Zealand 2023. These findings could be valuable to benchmark the contemporary positional demands of women`s international football, while also providing a framework to design role-specific training drills.